1999
DOI: 10.1051/aas:1999435
|View full text |Cite|
|
Sign up to set email alerts
|

The Local Group dwarf irregular galaxy IC 1613

Abstract: Abstract. We obtained U -band photometry of 1500 stars and BV -band photometry of 3100 stars in a field centred on the HII regions of the northeast sector of the dwarf irregular galaxy IC 1613 -a member of the Local Group. The ages of the stellar populations were determined from the ((B − V ) 0 , M V ) color-magnitude using the isochrones from Padua's library. The stellar populations were split into three groups: the group of the youngest stars with ages of between 5 and 20 Myr, the group of intermediate stars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 25 publications
0
48
1
Order By: Relevance
“…The associations we have found follow the same distribution as Hodge (1978)'s, but our code breaks them into many smaller ones. Georgiev et al (1999) observed the same effect in their results for the bubble area of the galaxy, and pointed out that their associations are the bright cores of Hodge's. We also find new associations both at the core of IC 1613 and the periphery.…”
Section: Comparison With Previous Cataloguesmentioning
confidence: 55%
See 4 more Smart Citations
“…The associations we have found follow the same distribution as Hodge (1978)'s, but our code breaks them into many smaller ones. Georgiev et al (1999) observed the same effect in their results for the bubble area of the galaxy, and pointed out that their associations are the bright cores of Hodge's. We also find new associations both at the core of IC 1613 and the periphery.…”
Section: Comparison With Previous Cataloguesmentioning
confidence: 55%
“…The youngest stars (age ∼ 10 Myr) are patchily arranged on the uniform underlying distribution of red stars (Freedman 1988;Battinelli et al 2007). In the bubble region, the young population can be split into 2 age groups of 5-20 Myr and 200-300 Myr (Georgiev et al 1999). The red supergiant stars in the region are massive (20-25 M ) and belong to the younger age group (Borissova et al 2000).…”
Section: Article Published By Edp Sciencesmentioning
confidence: 99%
See 3 more Smart Citations